2020
DOI: 10.3389/fpsyg.2020.567522
|View full text |Cite
|
Sign up to set email alerts
|

A Postcard From Italy: Challenges and Psychosocial Resources of Partners Living With and Without a Chronic Disease During COVID-19 Epidemic

Abstract: The new Coronavirus (COVID-19) has been declared a global pandemic by the World Health Organization (WHO). The sudden outbreak of this new virus and the measure of lockdown adopted to contain the epidemic have profoundly changed the lifestyles of the Italian population, with an impact on people’s quality of life and on their social relationships. In particular, due to forced and prolonged cohabitation, couples may be subject to specific stressors during the epidemic. In addition, living with a chronic health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 62 publications
(71 reference statements)
2
27
0
2
Order By: Relevance
“…This result may reflect complex relationships between pre-pandemic mental, physical, and social health; COVID-19 illness; and isolation's effects on mental and relationship health. Multiple studies have propounded significant associations between pre-existing physical conditions and psychological distress during the pandemic (Iob et al, 2020;Rapelli et al, 2020;Salari et al, 2020;Wang et al, 2020). These psychological conditions may further increase risk of COVID-19 illness in vulnerable GBMSM populations-early pandemic research has observed that those with pre-existing psychiatric conditions are more susceptible to coronavirus infection (Taquet et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result may reflect complex relationships between pre-pandemic mental, physical, and social health; COVID-19 illness; and isolation's effects on mental and relationship health. Multiple studies have propounded significant associations between pre-existing physical conditions and psychological distress during the pandemic (Iob et al, 2020;Rapelli et al, 2020;Salari et al, 2020;Wang et al, 2020). These psychological conditions may further increase risk of COVID-19 illness in vulnerable GBMSM populations-early pandemic research has observed that those with pre-existing psychiatric conditions are more susceptible to coronavirus infection (Taquet et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additional pandemic-related stressors and behaviors that have previously been associated with relationship characteristics and quality were measured: employment change (Balzarini et al, 2020;Biddle et al, 2020;Halliday Hardie & Lucas, 2010;Schmid et al, 2020;Vinokur et al, 1996;White & Rogers, 2000); chronic/ pre-existing health conditions (associated with higher risk of serious COVID-19 illness) and COVID-19 case history (Hagedoorn et al, 2000;Rapelli et al, 2020;Traa et al, 2015;Whisman et al, 2004); and changes in substance use (Stephenson et al, 2021) and anal intercourse (AI) frequency (Shilo & Mor, 2020;Stephenson et al, 2021). Respondents reported whether they had a pandemic-related change in employment (fired/laid off/ furloughed from [their] job/or lost work, still employed but at reduced hours/workload, or other change); those who responded affirmatively were considered to have experienced pandemic-related employment changes.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Under the outbreak, further attention to be paid to public health, both physical and psychological, to help communities during this challenging period (71)(72)(73). The COVID-19 outbreak has brought many extra challenges to the study, planning, and management of health (4,74,75). The problems of COVID-19 mental health and bureaucratic responses to the outbreak are not exactly unprecedented.…”
Section: Challenges and Recommendations Concerning The Psychological Impact Among Ckd Patientsmentioning
confidence: 99%
“…Evidence supports the view that cardiac patients suffer from stress in managing their clinical condition ( Jackson et al, 2018 ). Still, illness management does not happen in isolation, and successfully coping with a cardiac disease significantly depends on the individual’s perceived social support, particularly that of the partner ( Donato et al, 2009 ; Iafrate et al, 2009 ; Rapelli et al, 2020c ). The partner usually provides emotional and practical support to the cardiac patient by constantly monitoring the patient’s medication adherence, making appointments, accompanying the partner to the regular medical visits, and detecting signs of cardiac symptoms.…”
Section: Introductionmentioning
confidence: 99%